POLA ASUH DAN INTERAKSI SOSIAL ANAK AUTIS DI SMP - SUCIANI, (Jurnal Pendidikan Khusus, 2016)
Abstract Taking care pattern of parents influenced so much the children’s development, one of them was the development in social interaction ability. One of the autism children’s disorders was disorder in social interaction. Therefore, to optimize the development of social interaction ability autism children the taking care pattern of parents which was suitable with the children’s needs was highly required. Based on this, the researcher did the research of taking care and social interaction of autism children. The purpose of this research was to describe the parents’ taking care pattern, social interaction of autism children, and the relationship between the parents’ taking care pattern and social interaction of autism children in SMPN 4 Sidoarjo. In this research the researcher used qualitative approach with descriptive kind of research. The research subject was autism children in SMPN 4 Sidoarjo numbering 4 children. The data collection method used observation and interview, and the technique of data validation used data triangulation. The research result indicated that parents’ taking care pattern of autism children in SMPN 4 Sidoarjo was two of four parents authoritative tendency whereas one was authoritarian tendency and another one was permissive tendency. The social interactive of autism children in SMPN 4 Sidoarjo from four autism children was two children had good social interaction and two others had enough social interaction. The conclusion of this research was that the autism children’s tendency with authoritative tendency taking care pattern had good social interaction whereas the autism children’s tendency with permissive and authoritarian tendencies taking pattern had enough social interaction.   Keywords: Taking care pattern, social interaction